2013
DOI: 10.1103/physrevlett.110.077401
|View full text |Cite
|
Sign up to set email alerts
|

Multiband Optical Absorption Controlled by Lattice Strain in Thin-FilmLaCrO3

Abstract: Experimental measurements and ab initio modeling of the optical transitions in strained G-type antiferromagnetic LaCrO(3) resolve two decades of debate regarding the magnitude of the band gap and the character of the optical absorption spectrum in the visible-to-ultraviolet (up to ∼5  eV) range in this material. Using time-dependent density functional theory and accounting for thermal disorder effects, we demonstrate that the four most prominent low-energy absorption features are due to intra-Cr t(2g)-e(g) (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 11 publications
(8 reference statements)
2
37
1
Order By: Relevance
“…After a slight decrease at approximately 3 eV, the absorption increases again in the UV range. The absorption spectrum of LVO can be well fitted by five broadened Gaussian peaks [37,38], and the peak positions are summarized in Table I. As shown in the inset of Fig.…”
Section: B Optical Absorption and Band Structurementioning
confidence: 93%
“…After a slight decrease at approximately 3 eV, the absorption increases again in the UV range. The absorption spectrum of LVO can be well fitted by five broadened Gaussian peaks [37,38], and the peak positions are summarized in Table I. As shown in the inset of Fig.…”
Section: B Optical Absorption and Band Structurementioning
confidence: 93%
“…At the time there was no additional experimental evidence clarifying the electronic structure of LaCrO 3 , but in 2013 Sushko et al 68 reported experimental measurements coupled with embedded cluster time-dependent DFT that discerned the multiple optical transitions present in this material. Spectroscopic ellipsometry revealed onset of absorption features near 2.3 eV and 3.2 eV, occurring before the large 5 eV optical absorption onset.…”
Section: B Electronic Structurementioning
confidence: 99%
“…Bulk LCO is an orthorhombic perovskite (space group Pbnm ) with lattice parameters a = 5.513 Å, b = 5.476 Å, c = 7.759 Å, and a pseudocubic parameter a = 3.885 Å (see schematic model in Figure S2a in the Supporting Information). Sushko et al have shown that the lowest energy excitation in LCO results from a t 2g 3 → e g 0 transition at ≈2.8 eV that is formally dipole forbidden. The O 2 p → Cr 3 d charge‐transfer excitation shows the strongest optical absorption and falls at ≈4.6 eV.…”
Section: Film Thickness (D) Room‐temperature Conductivities (σ) Actmentioning
confidence: 99%
“…Based on time‐dependent density functional theory calculations of the excitation energies and corresponding intensities, feature A is assigned to the dipole forbidden t 2g 3 → e g 0 excitation, as shown schematically in Figure c. The extrapolated forbidden bandgaps are plotted in the inset of Figure a.…”
Section: Film Thickness (D) Room‐temperature Conductivities (σ) Actmentioning
confidence: 99%